MENGUAK NILAI FALSAFAH TALLU LOLONA: LOLO TAU DALAM PEMBERDAYAAN ANGGOTA CREDIT UNION SAUAN SIBARRUNG - Fransiskus Randa; Fransiskus E. Daromes; Yulianus Bottong (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2023)
This study aims to uncover one of the philosophical values of Tallu lolona, namely lolo tau (human shoots) in an effort to increase the empowerment of cooperative members as part of the process of re-actualizing local cultural values of an area. The research was conducted in one of the cooperatives located in the Tana Toraja area which has strong cultural values.This study uses a qualitative approach using ethnographic methods and uses one of the Tallu Lona philosophy, namely Lolo Tau in Toraja society as an analytical tool. The data was collected through in-depth interviews with several key informants, field observations and the collection of cultural artifacts in the field. The object of the research was the Sauan Sibarrung CU cooperative in managing the resources of its members.The meaning of the lolo tau philosophy in the management of the Sauan Sibarrung CU is an effort to humanize humans which is internalized in educational activities, empowerment and solidarity. Internalization of education is carried out so that members of the Sauan Sibarrung CU understand the nature of the CU and understand the rights and obligations of each member. This educational activity is seen as the main internalization of lolo tau in order to be able to improve their quality of life independently. Another internalization is empowerment. Empowerment is intended so that members can improve their standard of living through empowering members individually or in groups. The third internalization is member solidarity through mutual cooperation programs in understanding the difficulties of its members when experiencing life difficulties, both in meeting the needs and dealing with the grief of members